Pemberian Kompres Air Hangat dan Rebusan Serai pada Lansia Penderita Nyeri Rheumatoid Arthritis di Panti Sosial Tresna Werdha Budi Luhur Jambi - Dwi Yunita Rahmadhani; Marnila Yesni; Yuliana Yuliana; Jufri Al Fajri; Dwi Kartika Pebrianti; Mila Triana Sari; Miko Eka Putri; Maimaznah Maimaznah; Vevi Suryenti Putri; Rahmi Dwi Yanti (Jurnal Abdimas Kesehatan (JAK), 2026)
Rheumatoid arthritis, a chronic inflammatory disease in the elderly, is characterized by pain, stiffness, and limited movement in the joints. One non-pharmacological effort that can be implemented is the application of warm water compresses and lemongrass decoction. The Community Service (PKM) activity aims to increase the elderly's knowledge regarding the management of rheumatoid arthritis pain and provide complementary therapy in the form of warm water compresses and lemongrass decoction. The activity was held at the Tresna Werdha Budi Luhur Social Home in Jambi, involving 40 participants, consisting of 35 elderly and 5 care workers. The method used was health education, discussions, demonstrations, and hands-on practice of applying warm water compresses and lemongrass decoction to elderly experiencing rheumatoid arthritis pain. Evaluation was conducted through observation of participant participation and the elderly's responses after the therapy. The results showed that 35 elderly reported reduced joint pain, increased physical comfort, and easier daily activities after receiving warm water compresses and lemongrass decoction. The care workers gained knowledge on how to administer the therapy so they could continue to apply it independently